Pengujian Alat Modifikasi Alternator Mobil Menjadi Listrik Rumah - Naufal Noverdi; Eka Sunitra; Maimuzar Maimuzar (Politeknik Negeri Padang, 2018)
This paper discusses the use of alternator cars into home electricity. This paper aims to overcome the energy crisis by reducing dependence on fossil energy sources by utilizing alternative energy sources or by developing technology in the form of alternator modifications, and also from this paper we can find out the optimum conditions of rotation and generating electricity. The workings of this alternator modification tool so as to produce electrical power that is using a motor as a drive connected to the alternator produced mechanical energy converted into electrical energy and from this alternator a voltage of 12 volts comes out and goes into travo to increase the voltage to 220 Volts. From the results of the testing of this final project, the effect of rotation on the production of electrical energy coming out on this alternator modification tool is if the rotation produced is high then the power output is also good and if the rotation is slowed the power coming out will also be small. The optimum condition of this test is at 1600rpm. Key words: keywords are written in 5 words which should be a subset of paper titles, written using lowercase letters except for abbreviations, and separated by comma punctuation for between words.